Food for thought or food for emotions? An analysis of marketing strategies in television food advertising seen by children in Colombia - Alcides Velasquez; Maria Fernanda Parra; Mercedes Mora-Plazas; Luis Fernando Gómez; Lindsey Smith Taillie; Francesca Renee Dillman Carpentier (Cambridge University Press, 2023)
Abstract Objective: To establish the relationship between the marketing strategies and nutritional quality of foods and beverages promoted in television food advertisements (TV ads) seen by Colombian child audiences overall and based on child gender and socio-economic strata (SES). Design: A quantitative content analysis of marketing appeals was combined with nutritional data of the food products advertised and matched with TV audience ratings data for each food and beverage ads for Colombian children between 4 and 11 years. Setting: All beverages and foods TV ads cable or over-the-air channels in Colombia in 2017. Participants: N/A. Results: Compared with rational appeals (e.g. freshness, health or nutrition messages), emotional appeals (referencing or depicting human senses or emotions, e.g. using cartoons to suggest fun) were more frequently used in the TV ads most viewed by Colombian children. Female children and children in lower SES tended to be more exposed to emotional appeals in TV ads than their male or higher SES counterparts. Furthermore, TV ads using more emotional appeals tended to be for products high in problematic nutrients. Conclusion: The findings of this study highlight the need to implement statutory measures to reduce the deleterious effect of food marketing on children.